Penerapan Massage Effleurage pada Lansia (Ny.N) dengan Nyeri Gastritis di Wilayah Kerja Puskesmas Putri Ayu, Kota Jambi - aulia, esasuryaaulia; Mekeama, Luri; Kamariyah, Kamariyah; Mawarti, Indah (Jurnal Ilmu Kesehatan Dharmas Indonesia, 2024)
The incidence of gastritis at the Putri Ayu Health Center occupies the seventh position out of the ten most non-communicable diseases with 1,260 cases (4.25%). Based on an initial survey at the Putri Ayu Health Center on May 27, 2024-June 7, 23 elderly people over the age of ≥ 60 years suffered from gastritis. One of the non-pharmacological pain treatments that can be done is massage effleurage. This case study aims to provide nursing care to the elderly (Mrs. N) with gastritis pain through massage effleurage in the Working Area of the Putri Ayu Health Center, Jambi City. The method used in this study is a case report. The innovation made by the researcher is the provision of massage effleurage to reduce the level of pain in Mrs. N in the work area of the Putri Ayu Health Center, Jambi City. The instruments used are the Numeric Rating Scale (NRS) and the standard operating procedure (SOP) for massage effleurage. Nursing care will be provided on June 3-8, 2024. After being given 5 meetings with massage effleurage, Mrs. N experienced a decrease in the pain scale from moderate pain (scale 5) to mild pain (scale 1). Non-pharmacological therapy massage effleurage is effective in lowering pain levels and this therapy can be applied independently or with the help of others in people with gastritis. Future research should be able to analyze cases using 2 or more patients that can be used as comparison materials to obtain more optimal results.